Constructing Brand Image and Product Quality in the Tea Industry: A Strategy to Increase Customer Loyalty through Customer Satisfaction - Novi Setyaningrum; Budi Setiawan; Dwi Retno Andriani (The University of Lampung, 2024)
The food and beverage industry, including Teh Botol Sosro products in Bojonegoro, contributes to greenhouse gas emissions, making it important to improve tea leaf quality through bioactivity and plant conservation. This study aims to prove that Teh Botol Sosro's brand image and product quality significantly influence customer satisfaction and loyalty. Using a quantitative design and SMARTPLS with 100 respondents, the results show that brand image (X1) has a direct effect of 33.40% on customer satisfaction (Z), while product quality (X2) has a direct effect of 46.50%. Customer satisfaction (Z) itself has the greatest impact on customer loyalty (Y) at 80.10%. Brand image and product quality also have an indirect effect on customer loyalty through satisfaction, with path coefficients ranging from 26.8% to 37.3%. In conclusion, PT Sinar Sosro should strengthen brand image and product quality to enhance customer loyalty through customer satisfaction. Keywords: Bioactivity; Increase loyalty; Sosro tea; Strengthening the brand image.